Comparative study of the synovial histology in rheumatoid arthritis, spondyloarthropathy, and osteoarthritis: influence of disease duration and activity. Issue 12 (1st December 2000) - Baeten, D; Demetter, P; Cuvelier, C; Van den Bosch, F; Kruithof, E; Van Damme, N; Verbruggen, G; Mielants, H; Veys, E M; De Keyser, F
Abstract : OBJECTIVES: To compare the macroscopic and microscopic characteristics of synovial tissue in rheumatoid arthritis (RA), spondyloarthropathy (SpA), and osteoarthritis (OA) after exclusion of possible biases induced by disease duration or activity, or both. METHODS: Synovial biopsy specimens were obtained by needle arthroscopy in patients with early RA (n=16), late RA (n=14), early SpA (n=23), and OA (n=12). Macroscopic and microscopic features were scored on a four point scale and analysed as a function of disease duration (early versus late RA), local and systemic disease activity, and diagnosis. RESULTS: Except for the maximal synovial lining thickness, no significant differences were seen between early and late RA. For disease activity, synovial histology was only weakly correlated with C reactive protein in RA, but seemed to be strongly dependent on effusion of the biopsied joint in all disease groups. After stratification for local disease activity, no disease related differences were found in patients without joint effusion. In contrast, important differences were found between patients with RA and SpA with active joint effusion. Synovial vascularity was macroscopically increased in SpA versus RA (p=0.017). A straight vessel pattern was only seen in RA, while tortuous vessels were preferentially seen in SpA. Vascularity was also microscopically increased in SpA compared with RA (p=0.031), and correlated with the macroscopic vascularity ( rs =0.36, p=0.036). CD3+ (p=0.008), CD4+ (p=0.008), and CD20+ (p=0.024) lymphocytes were overrepresented in RA compared with SpA. The integrin expression in RA was characterised by a decrease of αVβ3 in the synovial lining (p=0.006) and an increase of αVβ5 in the sublining (p<0.001). CONCLUSIONS: The immune architecture of the synovial membrane is more dependent on local disease activity than on disease duration. Synovium obtained from clinically affected joints shows important histological differences between RA and SpA.